2016
DOI: 10.1108/mhrj-10-2014-0039
|View full text |Cite
|
Sign up to set email alerts
|

The short term effectiveness of day treatment for eating disorders in reducing psychosocial impairment: utilizing the clinical impairment assessment in routine practice

Abstract: Purpose-The purpose of this paper is to investigate the effectiveness of a day treatment programme (DTP) in reducing psychosocial impairment, changing attitudes, restoring bodyweight and decreasing binge/vomit symptoms among 52 individuals (aged 16+) with eating disorders. It was hypothesized that day treatment would result in improvements across all variables measured. Design/methodology/approach-In a within-participants design, demographic, physiological and psychological measures were taken on admission to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…This increases opportunities for young people to practice new skills in their home environment and everyday life, as opposed to the more restricted environment of an inpatient or residential model of care. The vast majority of published literature on day treatments concerns adult populations (Abbate‐Daga et al, ; Zipfel et al, ) or mixed adult and adolescent populations (Dancyger et al, ; Green et al, ; Hepburn & Clark‐Stone, ) however, in recent years literature concerning adolescents is increasing (Bryson, Scipioni, Essayli, Mahoney, & Orstein, ; Goldstein et al, ; Herpertz‐Dahlmann et al, ; Hoste, ; Johnston, O'Gara, Koman, Baker, & Anderson, ; Ornstein, Essayli, Nicely, & Masciulli, ; Ornstein, Lane‐Loney, & Hollenbeak, ). For a review see Friedman et al ().…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This increases opportunities for young people to practice new skills in their home environment and everyday life, as opposed to the more restricted environment of an inpatient or residential model of care. The vast majority of published literature on day treatments concerns adult populations (Abbate‐Daga et al, ; Zipfel et al, ) or mixed adult and adolescent populations (Dancyger et al, ; Green et al, ; Hepburn & Clark‐Stone, ) however, in recent years literature concerning adolescents is increasing (Bryson, Scipioni, Essayli, Mahoney, & Orstein, ; Goldstein et al, ; Herpertz‐Dahlmann et al, ; Hoste, ; Johnston, O'Gara, Koman, Baker, & Anderson, ; Ornstein, Essayli, Nicely, & Masciulli, ; Ornstein, Lane‐Loney, & Hollenbeak, ). For a review see Friedman et al ().…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, there is variability in length of treatment, as well as the expected short and long term outcomes. Despite these variations, common findings indicate that day programs enhance treatment and improve physical and psychological outcomes for young people who are not progressing in outpatient treatment (Girz, Lafrance Robinson, Foroughe, Jasper, & Boachie, 2013;Goldstein et al, 2011;Green et al, 2015;Grewal, Jasper, Steinegger, Yu, & Boachie, 2013;Henderson et al, 2014;Hepburn & Clark-Stone, 2016;Hoste, 2015;Ornstein et al, 2012;Ornstein et al, 2017), are no less effective in this respect than inpatient care (Herpertz-Dahlmann et al, 2014) and have treatment gains maintained at follow up (Bryson et al, 2018). This paper reports on a chart review of young people referred to the Intensive Treatment Program (ITP) at the Maudsley Hospital in London in the first four and a half years of its operation.…”
Section: Introductionmentioning
confidence: 99%
“…This study aimed to build upon and extend findings from an earlier study (Hepburn and Clark-Stone, 2016) which was conducted at the same DTP during an overlapping timeframe. The former study found that among participants who were deemed to have completed the DTP, psychosocial impairment reduced, eating disorder attitudes improved, underweight participants increased their body mass index (BMI) and participants with binge/vomit symptoms reduced these behaviours between admission to and discharge from the DTP.…”
Section: Introductionmentioning
confidence: 97%
“…Evidence indicates that DTPs are effective at treating adults with anorexia nervosa and bulimia nervosa through reducing eating disorder psychopathology and disordered behaviours, restoring patients’ weight, and reducing anxiety and depression (Abbate-Daga et al , 2015; Beintner et al , 2019; Ben-Porath et al , 2010; Brown et al , 2018; Crino and Djokvucic, 2010; Fittig et al , 2008; Freudenberg et al , 2016; Garte et al , 2015; Hepburn and Clark-Stone, 2016; Jones et al , 2007; Kong, 2005; Olmsted et al , 2003, 2013; Reisch et al , 2001; Schaffner and Buchanan, 2008; Wade et al , 2019; Willinge et al , 2010; Zipfel et al , 2002). Although symptom frequencies often remain within the clinical parameters specified by the Fifth Edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) (American Psychiatric Association, 2013) at the end of day treatment (Hepburn and Wilson, 2014), evidence suggests that treatment gains can be maintained or further improved at 3 months (Wade et al , 2019 ; Willinge et al , 2010), 6 months (Reisch et al , 2001), 12 months (Abbate-Daga et al , 2015), 18 months (Fittig et al , 2008), 24 months (Brown et al , 2018) and 26 months (Beintner et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Day treatment programs can therefore potentially improve social and occupational domains, in addition to eating disorder and psychiatric symptomatology. For example, individuals ages 16 and above who attended a specialized eating disorder day treatment program reported significant improvements in psychosocial functioning, including work performance (Hepburn & Clark-Stone, 2016). Assessment of occupational performance, in addition to eating disorder symptomatology, is thus warranted as part of treatment outcome measurements.…”
mentioning
confidence: 99%